Asymptotic Dichotomy in a Class of Odd-Order Nonlinear Differential Equations with Impulses. (22nd December 2013) - Wen, Kunwen; Pan, Lijun
Abstract : We investigate the oscillatory and asymptotic behavior of a class of odd-order nonlinear differential equations with impulses. We obtain criteria that ensure every solution is either oscillatory or (nonoscillatory and) zero convergent. We provide several examples to show that impulses play an important role in the asymptotic behaviors of these equations.